2015
DOI: 10.3390/ijerph120605862
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of the Economic Frontier and the Diffusion of Violence in the Amazon

Abstract: Over the last few decades, the occupation of the Amazon and the expansion of large-scale economic activities have exerted a significant negative impact on the Amazonian environment and on the health of the Amazon’s inhabitants. These processes have altered the context of the manifestation of health problems in time and space and changed the characteristics of the spatial diffusion of health problems in the region. This study analyzed the relationships between the various economic processes of territorial occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
(26 reference statements)
0
14
0
2
Order By: Relevance
“…Undoubtedly though, the results of our analysis set up the conditions for understanding how crime is perceived within indigenous villages and whether there were observations of increased crimes within their villages that have not been reported in the newspaper we examined. As efforts are ongoing to map crime [24], from environmental [22] to homicides [23] across Amazonia, our future work will continue this movement to understand how crime impacts indigenous peoples influenced landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Undoubtedly though, the results of our analysis set up the conditions for understanding how crime is perceived within indigenous villages and whether there were observations of increased crimes within their villages that have not been reported in the newspaper we examined. As efforts are ongoing to map crime [24], from environmental [22] to homicides [23] across Amazonia, our future work will continue this movement to understand how crime impacts indigenous peoples influenced landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…In the final analysis, our work shows that guns and crime patterns have shifted towards indigenous peoples' influenced landscapes. The porous nature of Guyana's borders makes knowing the direction from which guns are arriving into the country a difficult task, but what is certain is that the center of gravity of such crime is changing, bringing violence closer to indigenous villages and, as Souza et al [23] observed, following the deforestation frontier. Furthermore, recent studies in North America [47] have shown that gun policy in the United States impacted the movement of guns to, and subsequently the levels of crime in, Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the expansion of these sectors often followed the traditional frontier mindset, in which natural ecosystems are replaced by other types of land use suited to quick economic gains with little concern for the local populations' traditions and culture (Becker 2001;. Third, there is evidence that the expansion of these sectors in the new Brazilian frontiers exacerbated social conflicts (Prates & Bacha 2011;Souza et al 2015) and did not always significantly contribute to the improvement of local human development .…”
Section: Land Usementioning
confidence: 99%